Digitization of Courts in Indonesia: Innovation or Barrier to Accessing Justice? (Indonesian Court and Justice Review, 2024)
The digitization of court systems in Indonesia has been hailed as a step forward in modernizing the judiciary, enhancing efficiency, and improving access to justice. However, questions remain about whether this shift represents genuine innovation or if it creates new barriers, especially for marginalized groups who may face difficulties navigating digital platforms. This study explores the impact of court digitization on the accessibility of justice in Indonesia, focusing on both the positive and negative aspects of this transformation. Through a mixed-methods approach, the research combines an analysis of legal documents and court practices with interviews from legal practitioners, court users, and technology experts. The findings highlight both the benefits of digitization, such as faster processing times and improved transparency, as well as challenges related to technological literacy, internet access, and the potential exclusion of certain segments of society. The novelty of this research lies in its examination of digitization from a critical perspective, considering not only the technological advancements but also their implications for equitable access to justice. The urgency of this issue is underscored by the growing reliance on digital systems in legal processes globally, and the need to ensure that digital solutions do not inadvertently marginalize those who are already vulnerable. This study contributes to the ongoing debate on digital justice, offering insights into how Indonesia can balance innovation with inclusivity in its pursuit of a fair and accessible judicial system.